2015
DOI: 10.4317/medoral.20307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the suture technique on postoperative pain, swelling and trismus after removal of lower third molars: A randomized clinical trial

Abstract: BackgroundTo evaluate the intensity of pain, swelling and trismus after the removal of impacted lower third molars comparing two different suture techniques of the triangular flap: the complete suture of the distal incision and relieving incision and the partial suture with only one suture knot for closure of the corner of the flap and the closure of the distal incision, without suturing the relieving incision.Material and MethodsA prospective, randomized, crossover clinical trial was conducted in 40 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 18 publications
2
15
0
2
Order By: Relevance
“…Escoda et al study shows that there are no statistically significant differences in trismus between the complete and partial closure. 5 In this study, a significant difference was observed in the amount of trismus on 2 nd postoperative day between primary and secondary closure.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Escoda et al study shows that there are no statistically significant differences in trismus between the complete and partial closure. 5 In this study, a significant difference was observed in the amount of trismus on 2 nd postoperative day between primary and secondary closure.…”
Section: Discussionmentioning
confidence: 55%
“…4 Primary and secondary closure is used for wound management after extraction of impacted lower third molars. 5 In primary healing, the socket is covered and sealed hermetically by a mucosal flap, whereas, in secondary healing, the socket remains in communication with the oral cavity. 4 Conflicting opinions have been expressed in the literature concerning these two types of healing.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers (12, 13, and 14) founded a significant difference in term of pain, swelling and trismus between the two techniques favoring the single suture techniques. In another study, researchers revealed no statistical significant difference between the two techniques (15) . Anighoro et al (16) showed a significant reduction in postoperative pain and trismus in single suture technique, however, no difference in the values of facial swelling when compared with multiple suturing technique.…”
Section: Single Suture Techniquementioning
confidence: 91%
“…e magnitude of these sequelae depends on the extent of inflammatory response resulting from the extent of tissue damage produced [7], which in turn depends on certain demographics including age, gender, oral health status, and anatomic and operative factors such as increased surgical difficulty, magnitude of ostectomy, and duration of surgery [7]. Different closure techniques with or without incorporation of drains [8]; use of drugs such as analgesics [9], corticosteroids [10], and antibiotics [11]; and physical therapeutic methods such as cryotherapy [12], soft laser application [13], and sutureless techniques [14][15][16][17][18] are among the number of modalities reported in the literature to minimize postoperative pain, swelling, and trismus. Damage to the capillary vessels and the release of inflammatory cytokines as a result of trauma lead to increased permeability of vessels and accumulation of serosanguineous fluid and exudate [16].…”
Section: Introductionmentioning
confidence: 99%
“…Sutureless closure with minimal manipulation of soft tissues and healing by secondary intention, decreasing time of surgery, leaving a self-drainage pathway for inflammatory exudate, and thereby reducing postoperative inflammation with impact on improving the oral health related quality of life index. Abundant data exists regarding the advantages of sutureless technique after third molar surgery like less pain, swelling, and trismus with comparatively few undesirable effects [5,7,[15][16][17][18] related to healing by secondary intention. In addition, there may be high potential for the formation of a periodontal pocket in relation to the adjacent second molar, but however, the literature is equivocal.…”
Section: Introductionmentioning
confidence: 99%